2023
DOI: 10.1038/s41598-023-43720-8
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike protein peptides displayed in the Pyrococcus furiosus RAD system preserve epitopes antigenicity, immunogenicity, and virus-neutralizing activity of antibodies

Victor Bolsanelli Cioffi,
Maria Fernanda de Castro-Amarante,
Aleksei Lulla
et al.

Abstract: Amongst the potential contribution of protein or peptide-display systems to study epitopes with relevant immunological features, the RAD display system stands out as a highly stable scaffold protein that allows the presentation of constrained target peptides. Here, we employed the RAD display system to present peptides derived from the SARS-CoV-2 Spike (S) protein as a tool to detect specific serum antibodies and to generate polyclonal antibodies capable of inhibiting SARS-CoV-2 infectivity in vitro. 44 linear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In addition, instead of using plaque or focus reduction neutralization test (PRNT or FRNT, respectively) to access the antibody neutralization titers, we used CPE‐VNT, a technique that has been successfully applied to measure serum NAbs both in humans and in other mammalian species. Although PRNT, and FRNT are considered golden standard, the CPE‐VNT has shown to be particularly useful for studying larger sets of samples 18,26,27 . The same technique has been used in our previous studies 13,14 and we preferred not to change the methodology in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, instead of using plaque or focus reduction neutralization test (PRNT or FRNT, respectively) to access the antibody neutralization titers, we used CPE‐VNT, a technique that has been successfully applied to measure serum NAbs both in humans and in other mammalian species. Although PRNT, and FRNT are considered golden standard, the CPE‐VNT has shown to be particularly useful for studying larger sets of samples 18,26,27 . The same technique has been used in our previous studies 13,14 and we preferred not to change the methodology in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…are considered golden standard, the CPE-VNT has shown to be particularly useful for studying larger sets of samples. 18,26,27 The same technique has been used in our previous studies 13,14 and we preferred not to change the methodology in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that this system was suitable for production of antibodies against extracellular loops of permeases from ABC transporters of Escherichia coli and Staphylococcus aureus without the need for expression and purification of complete membrane proteins [6]. The system also was applied to evaluate the immunogenicity of sequences from SARS-CoV-2 Spike protein, production of antibodies and selection of antibodies with ability to neutralize the virus infection in human cells [7].…”
Section: Introductionmentioning
confidence: 99%